Translating immunology into therapeutic concepts for inflammatory bowel disease - Uhlig, HH; Powrie, F (Annual Reviews, 2018)
Inflammatory bowel disease (IBD) defines a spectrum of complex disorders. Understanding how environmental risk factors, alterations of the intestinal microbiota, and polygenetic and epigenetic susceptibility impact on immune pathways is key for developing targeted therapies. Mechanistic understanding of polygenic IBD is complemented by Mendelian disorders that present with IBD, pharmacological interventions that cause colitis, autoimmunity, and multiple animal models. Collectively, this multifactorial pathogenesis supports a concept of immune checkpoints that control microbial-host interactions in the gut by modulating innate and adaptive immunity, as well as epithelial and mesenchymal cell responses. In addition to classical immunosuppressive strategies, we discuss how resetting the microbiota and restoring innate immune responses, in particular autophagy and epithelial barrier function, might be key for maintaining remission or preventing IBD. Targeting checkpoints in genetically stratified subgroups of patients with Mendelian disorder-associated IBD increasingly directs treatment strategies as part of personalized medicine.